Simultaneous (two‐surgeon) versus staged bilateral knee arthroplasty: an observational study of intraoperative and post‐operative outcomes. Issue 5 (27th February 2020) - Gill, Stephen D.; Hill‐Buxton, Leaha‐Marie; Gwini, Stella May; Morrison, Stewart; Moreira, Brett; Beattie, Sally; Thomson, Andrew; Page, Richard S.
Abstract: Background: The advantages of simultaneous bilateral total knee arthroplasty (sim‐BTKA) remain controversial. This study investigated the effects of two‐surgeon sim‐BTKA compared to separate admission staged BTKA regarding intraoperative and post‐operative outcomes and health service costs. Methods: Patients underwent sim‐BTKA or staged BTKA between 1 November 2008 and 30 June 2016. Data were extracted from a joint replacement registry and medical records. Median regression and chi‐squared tests were used for between‐group comparisons. Results: Median hospital total length of stay was 5 days less for sim‐BTKA ( n = 122) than staged BTKA group ( n = 46) (7 versus 12; 95% confidence interval (CI) 3.9, 6.1), and 9 days less for inpatient rehabilitation (17 versus 26; 95% CI 3.7, 14.3). However, 80% of sim‐BTKA patients went to inpatient rehabilitation (versus 27% following staged BTKA), so median total length of stay was 9 days less for staged BTKA (13 versus 22; 95% CI −12.8, −5.2). Total anaesthesia time was 135 min less for sim‐BTKA ( P  < 0.001), while staged BTKA required less blood transfusions ( P = 0.001). Complication rates were similar, except for superficial infections which were observed twice as often after staged BTKA (30% versus 15%, P = 0.048). Twelve months following sim‐BTKA and the first staged total knee arthroplasty, sim‐BTKA had better WOMAC pain, stiffness and function scores ( P  ≤ 0.05). Average inpatient costs (hospital and rehabilitation) were $6388 less for sim‐BTKA. Conclusion: Sim‐BTKA appears to be a comparatively safe alternative to staged BTKA. Sim‐BTKA may be superior to staged BTKA due to faster improvements in pain and function and lower healthcare costs. How these results generalize to other health services requires further investigation. Abstract : When compared to staged bilateral total knee arthroplasty, simultaneous bilateral total knee arthroplasty patients had faster improvements in pain and function, shorter total acute hospital length of stay and lower health service costs.